Convection inhibition energy of the inversion and the suppressed rainfall over the Arabian Sea during July 2002 - BHAT, G. S. (MAUSAM, 2005)
All India rainfall was an unprecedented 49% below normal in the peak monsoon month of July in the year 2002. Surface and upper air conditions that prevailed over the Arabian Sea 100-200 km off the west coast of India during July 2002 are described here using the data collected from ORV Sagar Kanya. The total amount of rainfall measured on the ship away from the coast was less than 30 mm in July. The surface conditions were conducive for the development of deep convection in the study area. Radiosonde profiles reveal a complex thermal structure in the vertical and on a majority of the days two prominent inversions were present, one near 800 hPa and the other near 500 hPa. The characteristics of the lower inversion, including the energy barrier that it created for the development of deep clouds is presented. It is shown that on most days during July first half, the convection inhibition energy in the lower inversion layer was much more than that an air parcel ascending moist adiabatically could overcome and the vertical growth of clouds was stunted. The second half of July is intriguing and more than one factor seems to have contributed to suppressed rainfall.